Tackling and Regulating Disasters. An Introduction - Tzaneva Elya (Comparative Southeast European Studies)
Today, disasters of different kinds are inseparable from the lives of individuals and of communities. They thrust themselves into people’s existence and bring chaos to organised society, as they challenge, disrupt and change the typical patterns of relations between people and their environment, both natural and social. This subject is positioned in the relatively newly established scientific field of disaster anthropology. Taken together, the articles included have made extensive use of research material to show that human communities and their cultures are formed under the influence of the natural environment, the physical and mental characteristics of the people in them and, accordingly, of the social and economic development they themselves create. The articles examine various questions and subjects and allow comparison of the existing danger of disaster and the vulnerability of the groups affected by disaster, and consider the construction of their behavioural responses in managing disaster, and their relations at official, institutional and personal levels. There is consideration too of changes in the social environment, and of the effects of disasters on the political and economic development of the countries and communities in which they occur.